Attention Deficit/Hyperactivity Disorder case (ADHD) and the medicalization of education: an analysis from parents and teachers' reports - Amancio Cruz, Murilo Galvao; Okamoto, Mary Yoko [UNESP]; Ferrazza, Daniele de Andrade (Univ Estadual Paulista-unesp, 2016)
Difficult behaviors in childhood are the center of frequent discussions in the medical and educational areas in the last years. Two interrelated phenomena stand out in this debate: the medicalization and pathologization of childhood. Medicine and psychiatry are known as producers of these processes creating and recreating diagnostic categories to justify innumerable problems in the complex relationships in the school environment. From this perspective, we intend to bring the narratives of parents and teachers from a public school in the state of Sao Paulo about students, aged between seven and 11 years old, diagnosed with Attention Deficit/Hyperactivity Disorder (ADHD) that link with discussions about the medicalization process in the present society. It is considered that children who have shown difficulties in learning or behaving are categorized as biological ahistorical bodies lacking social and affective life.
Keywords: ADHD; Medicalization; Childhood; Parents; Teachers